2020
DOI: 10.1016/j.omtn.2020.07.032
|View full text |Cite
|
Sign up to set email alerts
|

USP10 Targeted Self-Deliverable siRNA to Prevent Scarring in the Cornea

Abstract: Ocular scarring after surgery, trauma, or infection leads to vision loss. The transparent cornea is an excellent model system to test anti-scarring therapies. Cholesterol-conjugated fully modified asymmetric small interfering RNAs (siRNAs) (selfdeliverable siRNAs [sdRNAs]) are a novel modality for in vivo gene knockdown, transfecting cells and tissues without any additional formulations. Myofibroblasts are a main contributor to scarring and fibrosis. a v integrins play a central role in myofibroblast pathologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 90 publications
(143 reference statements)
0
6
0
Order By: Relevance
“…Previous studies established the cross-talk between USP10 and fibrosis in multiple tissues, which are down-regulated in cancers, Parkinson disease (PD), and keloids, and specifically render the heart susceptible to hypertrophy injury ( Anisimov et al, 2019 ; Deng et al, 2019 ; Boumil et al, 2020 ; Zhang et al, 2020 ). These studies provided compelling evidence confirming the role of USP10 in cardiac hypertrophy, and indicated that USP10 inhibition exacerbated pressure overload-induced cardiac dysfunction and facilitated angiotensin II-induced cardiomyocyte injury.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies established the cross-talk between USP10 and fibrosis in multiple tissues, which are down-regulated in cancers, Parkinson disease (PD), and keloids, and specifically render the heart susceptible to hypertrophy injury ( Anisimov et al, 2019 ; Deng et al, 2019 ; Boumil et al, 2020 ; Zhang et al, 2020 ). These studies provided compelling evidence confirming the role of USP10 in cardiac hypertrophy, and indicated that USP10 inhibition exacerbated pressure overload-induced cardiac dysfunction and facilitated angiotensin II-induced cardiomyocyte injury.…”
Section: Discussionmentioning
confidence: 99%
“…It also decreased fibrotic marker (fibronectin and α-SMA) expression and αVβ1,5 integrin expression on the surface of corneal fibroblasts [ 70 ]. Bowmil et al [ 71 ] used a self-deliverable siRNA (siRNA) targeting USP10 conjugated to cys3 and cholesterol to treat wounded rabbit corneas. These siRNAs could penetrate to a depth of 324 µm in the corneal stromal layer within 24 h of transfection and reduce the expression of collagen III and fibrotic markers.…”
Section: Regeneration Of Scarless Corneamentioning
confidence: 99%
“…4 Myofibroblasts are the main contributor to excessive extracellular matrix deposition leading to scar formation and fibrosis. 5 Upon injury, transforming growth factor-β1 (TGF-β1) is released into the corneal stroma 6 and activates keratocytes, the quiescent resident cells in the corneal stroma. Activated keratocytes are differentiated into fibroblasts and further matured into myofibroblasts.…”
Section: Introductionmentioning
confidence: 99%